Macrophages Are the Key Players in Promoting Hyper-Inflammatory Response in a Mouse Model of TB-IRIS - Pal, Lalit; Nandani, Raj; Kumar, Pawan; Swami, Bharati; Roy, Gargi; Bhaskar, Sangeeta (Frontiers in Immunology, 2021)
TB-IRIS is an abnormal inflammatory response in a subset of HIV-TB co-infected patients shortly after initiation of anti-retroviral therapy (ART). Therapy in these patients could have greatly improved the life expectancy as ART reconstitutes the function and number of CD4+T cells and many patients see improvement in symptoms but paradoxically up to 54% of co-infected patients develop TB-IRIS. Different studies have indicated that both innate and adaptive immunity are involved in the pathology of IRIS but the role of macrophages in abnormal activation of CD4+T cells is poorly understood. Since macrophages are one of the major antigen-presenting cells and are infected by M.tb at a high frequency, they are very much likely to be involved in the development of TB-IRIS. In this study we have developed a mouse model of experimental IRIS, in which M.tb infected T cell knock-out mice undergo a fatal inflammatory disease after CD4+T cell reconstitution. Lung macrophages and blood monocytes from M.tb infected TCRβ−/− mice showed up-regulated expression of cell surface activation markers and also showed higher mRNA expression of inflammation-associated chemokines and matrix metalloproteases responsible for tissue damage. Further, cytokine and TLR signalling feedback mechanism to control excessive inflammation was also found to be dysregulated in these macrophages under lymphopenic conditions. Previous studies have shown that hyperactive CD4+T cells are responsible for disease induction and our study shows that somehow macrophages are in higher activated state when infected with M.tb in an immune-deficient condition which results in excessive activation of the adoptively transferred CD4+T cells. Understanding of the mechanisms underlying the pathophysiology of TB-IRIS would facilitate identification of prospective biomarkers for disease development in HIV-TB co-infected patients before starting antiretroviral therapy.